A computer-based optimal distribution substation and primary feeder planning - Sadain, Said K. (1984)
A Fixed Charge Generalized Network Problem (FCGNP) for solving the electric distribution system planning problem is formulated. The model is unique in that it introduces loss constraints in addition to the traditional considerations for fixed charges, variable costs, capacity limits and the conservation of power flow. A branch-and-bound procedure using the generalized network model as fathoming device is coded into a computer software program to solve the problem of optional distribution substation siting and sizing, primary feeder routing. The branch-and-bound procedure adapts a dominance criterion, a priority scheme and validity tests due to a fixed cost upper bound and source sufficiency, to improve its computational efficiency. Results of program implementation on test systems are reported and compared with those obtained from the use of the traditional pure network flow problem formulation. Experience with the program indicates that the proposed model is feasible (in terms of computing time) and superior than the pure network flow model (in terms of quality of the solution network).